KONFLIK SOSIAL MASYARAKAT DENGAN PERUSAHAAN SAWIT ECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Endang Peryadi; Fatmawati Fatmawati; Pabali Musa (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
Abstract The research is related to the problem of Social Conflict between the Community and Palm Oil Company in Batu Ampar Sub-district, Kubu Raya Regency. The problem is why social tension occurs between the oil palm plantation company and the local community in Batu Ampar Sub-district. The theory used by Marx aims to describe the social conflict between the community and the owner of palm oil plantation company. The method used is descriptive research that aims to explain intensively about the research in question. It includes the background of the current situation, and the environmental interaction of a social unit: individuals, groups, institutions, or communities. The conclusion from the findings of this research about social conflict between PT. Fajar Saudara Lestari Oil Palm Plantation and the community of Batu Ampar Villages, Batu AMpar Sub-District, Kubu Raya Regency is expected to provide input to various parties. Social conflict between PT. Fajar Saudara Lestari Oil Palm Plantation and the community is due to changes in the socio-economic structure of the community from the capacity system through patterns for business. As a result of the entry o the oil palm plantation, there is a grouping of people over the structure of resources, including: groups that have the power of economic resources and groups that have social resources. Key words : Social conflict, Oil Palm Plantation Farmers, Batu Ampar-Kubu Raya